Crescimento de mudas de guabijuzeiro em diferentes condições luminosas - Voss, Larissa Corradi (2020)
The guabijutreeis a native fruit tree, belonging to the Myrtaceae family, which it produces edible fruits with high consumption potential for innatura orindustryuse. However, this potential is poorly explored, which it may be due to the lack of technical knowledge for the management of the species, especially in the production of quality seedlings, as it is the first step in the process for orchard implanting. One of the factors to be observed in the production of seedlings is the light intensity favorable for proper growth and development, considering that the species occurs naturally in the forest. The objective of this work was to evaluate thegrowth of guabiju seedlings under different conditions of light intensity. The research was carried out Unidade de Ensino e Pesquisa Viveiro de Plantas Hortícolas, atEstação Experimental ofUniversidade Tecnológica Federal do Paraná-Câmpus Dois Vizinho, Paraná State, Brazils. The guabiju seedlingsfrom seeds were transplanted to20-liter pots, and it was accommodated in structures with screens of shading of different light intensities,besides área in full sun and ofnatural shading. The experimental design used was in blocks completely randomized, in a 5 x 6 bifactorial (seasons x shadows), 4 replicateswith 5 pots per experimental unit. The treatments were based on the luminous intensity used, it being these a condition of full sun; natural shading; shading intensity of 35% with black screen; shading intensity of 35%, with red photoconverter screen; 50% shading intensity with black screen; shading intensity of 80%, with black screen. The growth variables analyzed were stem and shoot length, stem diameter, number of young leaves, length of primary shoots, total chlorophyll content, leaf area, dry shoot mass, shootdiameter, total plant size, number of secondary roots,root system size. Dry root matter mass,root systemvolume and root system architecture and seedling quality index. Besides theclimatic variables temperature, relative humidity, light intensity and rainfallwere evaluated. Evaluations were carried out each season of the year, to determine the levels of total sugars and proteinsleaf. After productionof the seedlingsin each light condition, they were transplanted to the field and evaluated for their initial establishment. For the growth of guabiju seedlings, the use of 35% black shading mesh or full sun conditions wererecommended. The spring and summer seasons showed greater growth of seedlings. In field conditions, the seedlings showed good adaptability, except for natural shading.